PENGARUH KAPASITAS SUMBER DAYA MANUSIA, PERENCANAAN PENGANGGARAN, POLITIK PENGAGGARAN, DAN INFORMASI PENDUKUNG DENGAN TRANSPARASI PUBLIK SEBAGAI VARIABEL MODERATING TERHADAP SINKRONISASI DOKUMEN APBD DENGAN DOKUMEN KUA-PPAS - Elfrina, Lidya; Ratnawati, Vince; Wiguna, Meilda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine the effect of the capacity of human resources, budgeting, planning, budgeting politics, and supporting information to the public as a moderating variable transparency to sync documents the local budget (budget) with the Public Policy Budget document (KUA) preliminary budget ceiling (PPAS ). The study population was a board member and officer / employee involved in the preparation of the Work Plan and Budget (RKA) Regional Working Units (on education) totaled 23 on education. The sampling technique using purposive sampling. Pengumpulam methods of data is the questionnaire. Analysis using multiple regression t test.The results of this study it is concluded that in partial capacity of human resources, budgeting, planning, budgeting politics, and supporting information berpengaruh significantly to the synchronization of the budget document by document KUA-PPAS. Test results indicate that the interaction of the Public Transparency can not moderate the relationship between human resource capacity, political budgeting, and supporting information to the budget document synchronization with KUA-PPAS documents, while the test results public transparency interactions may moderate the relationship between budgeting planning to synchronize with the budget document KUA-PPAS documents.Keywords: budget, KUA-PPAS, Human Resource Capacity Planning Budgeting, Politics Budgeting, Information Supporters, Transparency Publik